Potential of Tetradenia riparia leaf essential oil and its fractions in controlling Aedes aegypti and Rhipicephalus microplus larvae (Bioscience Journal, 2023)
Tetradenia riparia (Hochst.) Codd (Lamiaceae) is a shrub, commonly known as ginger bush or false myrrh, and several studies have shown that T. riparia exhibits a variety of biological properties. This study aimed to determine the chemical composition of T. riparia essential oil and its fractions, investigate their anticholinesterase activity, and assess their larvicidal activity against the cattle tick Rhipicephalus microplus and the mosquito Aedes aegypti. Eleven essential oil fractions were obtained by fractionation and analyzed by gas chromatography/mass spectrometry. Larvicidal activity against R. microplus and third-instar A. aegypti was assessed using a larval packet test and a larval immersion test, respectively. Anticholinesterase activity was determined by a bioautographic method. Forty-nine compounds were identified in the essential oil, of which the major classes were oxygenated sesquiterpenes (45.95%) and sesquiterpene hydrocarbons (35.20%) and the major components were isospathulenol (17.40%), β-caryophyllene (15.61%), 14-hydroxy-9-epi-caryophyllene (10.07%), 14-hydroxy-α-muurolene (8.32%), and 9β,13β-epoxy-7-abietene (5.53%). Bioassays showed that T. riparia essential oil (LC50 = 1.56 µg/mL) and FR3 (LC50 = 0.30 µg/mL) were the most active against R. microplus and A. aegypti larvae, respectively. The essential oil and FR1, FR2, and FR3 exhibited acetylcholinesterase inhibitory activity. These results indicate that T. riparia essential oil and its fractions hold promise in the development of novel, environmentally safe agents for the control of R. microplus and A. aegypti larvae.